PELATIHAN KERAJINAN TAS TALI KUR DALAM MENINGKATKAN KETERAMPILAN PEREMPUAN DI DESA GRINTING SIDOARDJO - Leo Khoiriyah Al Agustin; Muhammad Irfan Hilmi, Lutfi Ariefianto, Deditiani Tri Indrianti, Arief Tukiman Hendrawijaya, Sylva A (JOURNAL OF COMMUNITY DEDICATION, 2025)
The program to improve the quality of life for women has a target, namely improving the quality and role of women in various fields. The Tali Kur bag craft training program was developed from the framework of the community empowerment pattern carried out in Grinting Village, Tulangan District, Sidoardjo Regency. Around the Tulangan sub-district, handicraft skills are still rare, especially those made from Tali Kur. This can help women to get additional activities and additional family economics in post-covid-19 conditions. The target of this service activity is 20 womens who are members of the PKK group. This training activity was carried out through 4 stages including; a) Planning; b) Organizing; c) Implementation; d) Follow-up. The training activity materials include a) Making basic bag patterns; b) Making bag motifs; c) Making a cover for the Bag; d) Provide croton for Bags; e) Installing zippers and slings; f) Bag packing; and g) Production of product labels. This service program is a form of education contribution to support environmental conservation and the use of local resources in improving women's skills and skills so that they can improve family welfare